Introduction to stochastic processes - Lawler, Gregory F. (Chapman & Hall probability series., 1995)
This text emphasizes key ideas and treats a number of advanced topics, such as Markov standard chains (discrete and continuous time) including branching process, optimal stopping, and reversible chains. It should be suitable for a first course in stochastic processes without measure theory.